Redesign of machine component in polymeric matrix composite towards increased productivity - Sá, Ricardo (2014)
This work is focused in the maximization of the acceleration a 2D Industrial Laser Cutting Machine (ILCM). The changes to be implemented are centered in the replacement of a metallic critical component: the gantry. This component largely influences precision and maximum acceleration. Finite Elements Analysis was performed to the current metallic part. From this analysis the maximum allowed deformations were established. A replacement composite component capable of an equally valid behavior was designed in carbon fiber. To establish the maximum increase in acceleration that does not lead to precision losses, the working conditions were simulated and the acceleration to which the component was subjected to was varied. The variation of the thickness of layers with different orientations and locations in the part allowed for the understanding of how the mass varies along with the maximum possible acceleration. This analysis, asides with considering the maximum force allowed by the linear motor that is responsible by the gantry motion, establishes the limit in terms of maximum acceleration of the machine. An increase of 22% in the maximum acceleration while maintaining the precision is possible due to the higher specific rigidity of composite materials and the use of an optimization heuristic.